Pengaruh Shopping Lifestyle, Fashion Involvement, dan Promosi Terhadap Impulse Buying Pakaian Bekas - Diyah Retno Ningrum; Ahmad Husin; Dian Noor Citra Perdana (ITB AAS Indonesia Surakarta, 2025)
This research seeks to assess how shopping habits, engagement with fashion, and promotional efforts influence spontaneous purchases at the Ada Ada Saja second-hand clothing store, both individually and collectively. This investigation employs a quantitative approach, utilizing literature reviews, and field research methods that include observations, interviews, and the distribution of questionnaires featuring a Likert scale. The application utilized for hypothesis testing is SPSS, which applies the t-test, F-test, R-test for analysis.